Nuts, cereals, seeds and legumes proteins derived emulsifiers as a source of plant protein beverages: A review. Issue 16 (7th September 2020) - Qamar, Sadia; Manrique, Yady J.; Parekh, Harendra; Falconer, James Robert
Abstract: Milk beverages derived from plant-based protein have attracted the interest of consumers and researchers as a health-promoting functional food. It can also be considered as a substitute for animal milk due to various allergy concerns associated with dairy milk. The plant-based emulsions are directed to prevent diet-related chronic diseases including diabetes, cardiovascular, obesity and other disorders due to the presence of healthy long-chain unsaturated fatty acids as compared to bovine milk. Further, associations between nutritional contents (vitamins, minerals and low fat) and pharmacological properties of plant-based protein may have extra beneficial effects. The review aims to summarize the four different groups of plant sources (nuts, cereals, seeds and legumes) used for the preparation of plant-based milk beverages. In addition, it also provides a detailed review of the general characteristics and functional properties of these plant sources. Physicochemical composition, protein and fats quality, functional properties, effect of heat and high-pressure treatment is also provided in detail. It also covers fats digestibility, protein stability, protein solubility and digestibility. Furthermore, the effect of processing, possible comparative study and potential applications in healthcare have been discussed.